Programs to improve teacher training in Argentine universities (2010-2015) Perspectives and experiences between the determinations of national policies and university autonomy (Praxis Educativa, 2024)
In this article we look into the ways of appropriation of the Human Sciences Support Project (PROHUM) in three Argentine national universities: those of La Plata, General Sarmiento and Luján. A collective case study of instrumental type was developed at a micro-social scale, triangulating data from institutional documents and in-depth interviews with authorities. The research sought to determine the degree of autonomy of these actors in the institutional definitions reached. Among the common measures, priority was given to the strengthening of positions assigned to pedagogical training subjects in teaching programs in the disciplines included in the PROHUM. The measures for the consolidation of teams for the initial stages of the careers also had a prominent place. Among the differences, the criteria that guided the decisions in each case stand out: the massiveness or the situation of dropout in the first years. In all three cases, a high degree of autonomy in defining improvements in teacher training was evident.
Keywords: educational programs; teacher training; national university; humanities; autonomy